Maternal exposure to fullerenols impairs placental development in mice by inhibiting estriol synthesis and reducing ERα - Qing He; Jiali Yuan; Huihui Yang; Ting Du; Siqing Hu; Ling Ding; Wei Yan; Panpan Chen; Jing Li; Zhenyao Huang (Journal of Nanobiotechnology)
Abstract Fullerenols, a water-soluble polyhydroxy derivative of fullerene, hold promise in medical and materials science due to their unique properties. However, concerns about their potential embryotoxicity remain. Using a pregnancy mouse model and metabolomics analysis, our findings reveal that fullerenols exposure during pregnancy not only significantly reduced mice placental weight and villi thickness, but also altered the classes and concentrations of metabolites in the mouse placenta. Furthermore, we found that fullerenols exposure reduced the levels of CYP3A4, ERα and estriol (E3), while increasing the levels of estradiol (E2) and oxidative stress both in mouse placenta and placental trophoblast cells, and exogenous supplementation with E3 and ER agonists was effective in restoring these changes in vitro. Moreover, CYP3A4 inhibition was effective in decreasing intracellular E3 levels, whereas overexpression of CYP3A4 resisted the fullerenols-induced decrease in E3 expression Additionally, we synthesized glutathione-modified fullerenols (C60-(OH)n-GSH), which demonstrated improved biocompatibility and reduced embryotoxicity by enhancing intracellular glutathione levels and mitigating oxidative stress. In summary, our results demonstrated that fullerenols exposure decreased E3 synthesis by inhibiting CYP3A4 and exacerbated oxidative stress through downregulation of estrogen receptor activation and decreased glutathione levels. These findings highlight the risks of fullerenols exposure during pregnancy and offer strategies for safer nanomaterial development.